Penerapan AES pada Sistem Keanggotaan Gym untuk Perlindungan Data Pribadi - Ananda, Deva Krishna; Mogi, I Komang Ari (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 1 (2023): JNATIA Vol. 2, No. 1, November 2023DO - 10.24843/JNATIA.2023.v02.i01.p12, 2023)
The security of gym member data files is an important aspect of maintaining the privacy and security of personal information stored in the gym management system. In this study, we propose the application of the Advanced Encryption Standard (AES) algorithm as a solution to secure gym member data files. AES is an encryption algorithm known for its high security and has been extensively used in information security applications. In this implementation, each gym member's data files, such as profiles, addresses, and other personal information, will be encrypted using a secret key that only the system knows. With encryption using AES, even if the member's data file is stolen or accessed illegally, the information contained in it remains safe and cannot be read without the correct secret key. The results of the trial found that this application succeeded in encrypting some member data files with .pdf format into the. rda format, then decrypting them back into the original file form without changing the original file size. So, it can be shown that the use of the AES algorithm in securing gym member data files provides a high level of security and protects sensitive information from unauthorized parties.